2022
DOI: 10.1101/2022.01.01.21268576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccination status is associated with physical activity in German-speaking countries: the COR-PHYS-Q cohort study

Abstract: BackgroundTo examine the association between COVID-19 vaccination status and physical activity (PA), sporting behavior, as well as barriers to PA in adults in Switzerland, Germany, and Austria.MethodsA total of 1516 adults provided complete responses to our online questionnaire sent out in August 2021. Information about self-reported PA categories, sporting behavior, barriers to PA, and COVID-19 vaccination status were gathered. Main analyses were done using multiple linear regression adjusted for relevant par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…COVID-19 vaccination status of patients might also affect VO 2peak . We previously demonstrated that physical activity, an important moderator of VO 2peak , differed between unvaccinated and fully vaccinated adults [80]. Finally, different methods to determine VE/ VCO 2 are available [56,81].…”
Section: Limitationsmentioning
confidence: 99%
“…COVID-19 vaccination status of patients might also affect VO 2peak . We previously demonstrated that physical activity, an important moderator of VO 2peak , differed between unvaccinated and fully vaccinated adults [80]. Finally, different methods to determine VE/ VCO 2 are available [56,81].…”
Section: Limitationsmentioning
confidence: 99%
“…The COVID-19 vaccination campaign, as per the case of the State of Qatar {A total of 256,037 individuals received at least one dose of the mRNA-1273 vaccine, and 181,304 completed the two-dose regimen [between 28 December 2020 and 10 May 2021, ( 12 )]}, has led to most people being more knowledgeable about vaccine effectiveness (e.g., preventing severe illness and death), as reported previously by Chemaitelly et al ( 12 ). One recent study of Schwendinger et al ( 13 ) found a significant association of vaccination status with total PA ( p = 0.011), vigorous PA ( p = 0.015), and moderate PA ( p = 0.001) in German speaking countries. For Ghram et al, ( 14 ) the availability of a vaccine might therefore help increase PA in the general population.…”
Section: Introductionmentioning
confidence: 94%